INTERNALISASI NILAI-NILAI HADITS TENTANG ADAB MENUNTUT ILMU DALAM PEMBELAJARAN DI MIN 5 BANDAR LAMPUNG - Muhammad Ilham Jaya Kesuma; Ilham Fatoni; A. Gani; Muhammad Akmansyah; Erjati Abas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Islamic education does not only focus on the dissemination of knowledge, but also on the formation of students' character. Internalization of the values ​​of the hadith about the etiquette of seeking knowledge, which include patience, respect for teachers, and sincerity, is an important component of Islamic education. However, in real life, these values ​​are still difficult to apply in formal educational institutions, such as Madrasah Ibtidaiyah Negeri (MIN) 5 Bandar Lampung. The purpose of this study was to see how the values ​​of the hadith about the etiquette of seeking knowledge are applied in learning at MIN 5 Bandar Lampung and how it impacts students' character. This study uses a qualitative approach with a field study method. The methods used to collect data are Observation, interviews with teachers and students, and analysis of documents related to madrasah education policies. Data analysis techniques use data reduction, data presentation, and drawing conclusions. The results of the study indicate that the internalization of the values ​​of the hadith in learning is carried out through teacher role models, habituation of discipline and respect for teachers, and integration of the values ​​of the hadith in the curriculum. The impact of this internalization is seen in the increase in students' religious and spiritual attitudes, politeness in interacting with teachers and peers, and increased motivation to learn. Therefore, the internalization of the values ​​of the hadith about the manners of seeking knowledge needs to be continuously strengthened through synergy between madrasas, teachers, and parents to create an educational environment that is more Islamic in character.